EXPERIENCES AND EXPECTATIONS OF NURSING TEACHERS RELATED TO THE COMPETENCY-BASED APPROACH IN GENERAL CARE TEACHING - Zunza Isenda Euloge; Mbelenge Mangombo Credo; Kafinga Luzolo Emery; Kazumba Sébastien; Palambwa Ansot Ruphine; Mukuwa Kakwata James; Norbert Kilewa Rashidi Kitoko; Alphonse Masandi Milondo (International Journal For Research In Health Sciences And Nursing, 2024)
This study aims to understand the experiences and expectations of teachers in the nursing science sector, in connection with the application of the skills-based approach in the “general care” course for the development of skills among learners. We conducted a qualitative descriptive study of the phenomenological type to explore the experience and expectations of nursing teachers from the “general care” course, interviewed on the application of the skills-based approach operating at the ISTM/Kinshasa. It is an exploration of a phenomenon through the individual members of the group. The results obtained show That : - general care course teachers perceive APC as an approach which places the learner at the center of their training and aims to develop the practical and theoretical skills necessary to apply to care and this implies an integration of knowledge, clinical skills and know-how, in order to train well-rounded health professionals ready to meet the challenges of nursing practice. With regard to the analysis of the representation of the experiences of nursing teachers in relation to their role as trainers, they showed that : - Teachers experience, on the one hand, pedagogical and didactic difficulties in the application of active teaching methods, and on the other hand, the difficulties of educational adaptation, of an institutional and financial nature.